1983
DOI: 10.1242/dev.73.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Lumen formation in the developing mouse mammary gland

Abstract: The mammary gland is a system of hollow interconnecting tubes which develops from an invasive branching cord of epithelial cells. This ultrastructural study of the developing mammary gland focuses on how the lumen forms and establishes the polarized epithelial lining of the gland. The earliest signs of lumen formation are many small cavities and crevices lined with microvilli which appear at scattered sites throughout the branching cords and neck of the gland. It is suggested that these initial small lumina fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In mice, branching morphogenesis begins when a sprout rooted to the embryonic surface ectoderm is induced to branch around E16 and yields a rudimentary tree of 10-20 branches by birth (E19-20) (Macias & Hinck 2012, Lindström et al 2022). Lumen formation commences shortly before birth, and soon after, the final, bilayered structure of mammary ducts is established (Hogg et al, 1983). The inner layer of cells enclosing the lumen and outer layer of cells separated from the mesenchyme by a basement membrane, begin to segregate into distinct luminal and basal lineages already during late embryogenesis (Lilja et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, branching morphogenesis begins when a sprout rooted to the embryonic surface ectoderm is induced to branch around E16 and yields a rudimentary tree of 10-20 branches by birth (E19-20) (Macias & Hinck 2012, Lindström et al 2022). Lumen formation commences shortly before birth, and soon after, the final, bilayered structure of mammary ducts is established (Hogg et al, 1983). The inner layer of cells enclosing the lumen and outer layer of cells separated from the mesenchyme by a basement membrane, begin to segregate into distinct luminal and basal lineages already during late embryogenesis (Lilja et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…1 C ). The presence of microluminae that begin to emerge at ∼E17.5 ( Hogg et al, 1983 ) was confirmed in the elongating tips of both 5-d cultured explants and E18.5 mammary glands ( Fig. S2, C and D ).…”
Section: Resultsmentioning
confidence: 71%
“…In mice, branching morphogenesis begins when a sprout rooted to the embryonic surface ectoderm is induced to branch around embryonic day 16 (E16) and yields a rudimentary tree of 10–20 branches by birth (E19-20; Macias and Hinck, 2012 ; Spina and Cowin, 2021 ; Lindström et al, 2022 Preprint ). Lumen formation commences shortly before birth, and soon after, the final, bi-layered structure of mammary ducts is established, and ductal tree continues to grow isometrically to the body size ( Hogg et al, 1983 ). The inner layer of cells enclosing the lumen and outer layer of cells separated from the mesenchyme by a basement membrane, begin to segregate into distinct luminal and basal lineages during late embryogenesis ( Lilja et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In hair follicles, the epithelium grows deeper into the dermis while encapsulating the dermal condensate that matures to dermal papilla, whereas the mammary bud gradually begins to proliferate and sprouts at ~E15.5 into a secondary mammary mesenchyme, the precursor of the adult fatty stroma, followed by onset of branching morphogenesis a day later . Mammary rudiments begin to branch as a solid cord of cells, and the bilayered ductal epithelium consisting of inner luminal and outer basal cells characteristic of the adult mammary gland becomes evident only after birth (Hogg et al, 1983;Myllymäki et al, 2023).…”
Section: Introductionmentioning
confidence: 99%